The role of the bacterial community in the nutritional ecology of the bulb mite Rhizoglyphus robini (Acari: Astigmata: Acaridae). Issue 4 (10th January 2013) - Zindel, Renate; Ofek, Maya; Minz, Dror; Palevsky, Eric; Zchori‐Fein, Einat; Aebi, Alexandre
Abstract : The biology of many arthropods can only be understood when their associated microbiome is considered. The nutritional requirements of the bulb mite Rhizoglyphus robini Claparede (Acari: Astigmata: Acaridae) in the laboratory have been shown to be very easily satisfied, and in the field the mites prefer fungus‐infected over uninfected plants. To test whether symbiotic bacteria facilitate the survival of R. robini on a temporarily nutritionally unbalanced diet, we investigated the composition of its microbiome. Using 454 pyrosequencing of 16S rRNA gene fragments, 3 genera were found to dominate the bacterial community: Myroides (41.4%), Serratia (11.4%), and Alcaligenes (4.5%); the latter 2 are known to include chitinase‐producing species. Laboratory experiments demonstrated that mite fecundity is significantly higher (2 times) on fungus than on controls (sterilized potato dextrose agar and filter paper). Also, when mite homogenate was applied to a chitin layer, the halo produced through degradation was clearly visible, while the saline control did not produce a halo. We thus concluded that R. robini utilizes fungal chitin, at least to a certain extent, as a food source with the help of its associated bacteria. This information supports the general concept of multigenome organisms and the involvement of bacteria in the mite's nutritional ecology.—Zindel, R., Ofek, M., Minz, D., Palevsky, E., Zchori‐Fein, E., Aebi, A. The role of the bacterial community in the nutritional ecology of the bulb mite Rhizoglyphus robini (Acari: Astigmata: Acaridae). FASEB J. 27, 1488–1497 (2013). www.fasebj.org